Arsanilic acid in growing-finishing swine rations - Koch, B.A.; Nam, T. (Kansas Agricultural Experiment Station, 2011)
Arsanilic acid is one of many feed additives approved by the Food and Drug Administration for use in swine rations. Results from an uncontrolled feeding demonstration suggested that arsanilic acid effectively increased daily gain and improved feed efficiency. This study was designed to check further the value of dietary arsanilic acid.
Keywords: Swine; Arsanilic acid; Daily gain; Feed efficiency